PAMELA - A model for an FFAG based hadron therapy machine - Peach, K; Cobb, J; Yokoi, T; Gardner, I; Edgecock, R; Poole, M; Pozimski, J; Cywinski, B; Jones, B; McKenna, G; Vojnovic, B; Fouwd, M; et al. (2007)
Approximately one third of the world's 15000 accelerators are used for tumour therapy and other medical applications [1]. The characteristics of FFAGs make them ideally suited to such applications, as the much smaller magnet size and greater compactness offers considerable cost and operational benefits. In the first stage the work on PAMELA will focus on the optimization of the FFAG design to deliver the specific machine parameters demanded by therapy applications. In this phase of the PAMELA project the effort win concentrate on the design of a semi-scaling type FFAGs to deliver a 450 MeV/u carbon ion beams including detailed lattice and tracking studies. The second stage win use the existing expertise in the BASROC consortium [2] to undertake a design of the magnets and RF system for PAMELA. An outline of the overall concept of PAMELA will be discussed and the actual status of the work will be presented.